Raw material for negative electrode material for non-aqueous secondary battery, negative electrode material for non-aqueous secondary battery, negative electrode for non-aqueous secondary battery, and non-aqueous secondary battery
A negative electrode material with controlled mercury intrusion and egress ratios stabilizes the structure, improving capacity and rapid charging performance by enhancing lithium ion diffusion and reducing swelling during charge/discharge cycles.
Patent Information
- Application Number
- JP2020059194
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-03-27
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2040-03-27
AI Technical Summary
Existing negative electrode materials for non-aqueous secondary batteries suffer from swelling during charge/discharge cycles, compromising their capacity and rapid charging characteristics.
A negative electrode material with controlled mercury intrusion and egress ratios (B/A) within specific ranges, combined with graphite and amorphous carbon, to stabilize the structure and enhance lithium ion diffusion.
The material provides high capacity, suppresses cycle swelling, and enhances rapid charging performance by promoting lithium ion diffusion and reducing residual stress.
Smart Images

Figure 0007615537000002 
Figure 0007615537000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a raw material for a negative electrode material for a non-aqueous secondary battery, a negative electrode material for a non-aqueous secondary battery, and a negative electrode for a non-aqueous secondary battery and a non-aqueous secondary battery that contain the negative electrode material for a non-aqueous secondary battery. [Background technology]
[0002] In recent years, the demand for high-capacity secondary batteries has been increasing along with the miniaturization of electronic devices. In particular, non-aqueous secondary batteries, especially lithium-ion secondary batteries, have attracted attention because of their higher energy density and superior rapid charge / discharge characteristics compared to nickel-cadmium batteries and nickel-metal hydride batteries. In particular, non-aqueous lithium secondary batteries consisting of positive and negative electrodes capable of absorbing and releasing lithium ions, and non-aqueous electrolytes in which lithium salts such as LiPF6 and LiBF4 are dissolved, have been developed and put to practical use.
[0003] Various materials have been proposed as negative electrode materials for non-aqueous lithium secondary batteries, and graphitic carbon materials such as artificial graphite obtained by graphitizing natural graphite or coke, graphitized mesophase pitch, and graphitized carbon fiber are used because of their high capacity and excellent flatness of discharge potential. Amorphous carbon materials are also used because they are relatively stable against some electrolytes. Furthermore, carbon materials are used in which amorphous carbon is coated or attached to the surface of graphite particles, combining the two characteristics of high capacity and small irreversible capacity due to graphite and excellent stability with electrolytes due to amorphous carbon.
[0004] Recently, in the field of electric vehicles and the like, characteristics such as high capacity and excellent low-temperature input / output characteristics are emphasized, and from these viewpoints, among the negative electrode materials of the above-mentioned non-aqueous lithium secondary batteries, materials in which amorphous carbon is coated or attached to the surface of graphite particles are used. Among such materials, Patent Document 1 discloses a negative electrode material in which amorphous carbon is coated under specific conditions and graphite is subjected to isotropic pressure treatment to improve rapid charging characteristics. In addition, Patent Document 2 discloses a negative electrode material with high capacity and improved charge / discharge characteristics by controlling the atomic concentration of sulfur and nitrogen elements present on the surface using coal tar pitch with a high quinoline content as a raw material for amorphous carbon to be coated on graphite particles. In addition, Patent Document 3 discloses a negative electrode material with low press load and improved low-temperature output characteristics due to a carbon material having specific thermal characteristics. Furthermore, Patent Document 4 discloses a negative electrode material that is coated with specific amorphous carbon and has a specific pore volume, thereby improving low-temperature input / output characteristics and high-temperature storage characteristics. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] WO2011 / 052452 [Patent Document 2] WO2012 / 157590 [Patent Document 3] JP 2017-045574 A [Patent Document 4] JP 2018-163868 A Summary of the Invention [Problem to be solved by the invention]
[0006] According to the study by the present inventors, it was found that the negative electrode materials for non-aqueous secondary batteries described in Patent Documents 1 to 4 cause plate swelling after charge-discharge cycles. The present invention provides a raw material for a negative electrode material for a non-aqueous secondary battery, which can provide a non-aqueous secondary battery having a large capacity, excellent rapid charging characteristics, and small plate swelling after charge / discharge cycles, and a negative electrode material for a non-aqueous secondary battery, and a non-aqueous secondary battery containing the same. [Means for solving the problem]
[0007] As a result of intensive research by the present inventors to solve the above problems, they have found that the above problems can be solved by a negative electrode material for a non-aqueous secondary battery using a graphite raw material, in which the ratio of mercury outflow / mercury inflow (B / A) measured by mercury intrusion porosimetry is controlled within a specific range. That is, the gist of the present invention is as follows.
[0008] [1] A raw material for a negative electrode material for non-aqueous secondary batteries that contains graphite and has a value of 45% or more in accordance with the following formula (1), where A is the amount of mercury injected and B is the amount of mercury released, as determined by mercury intrusion porosimetry. Formula (1) B / A×100(%) [2] The raw material for a negative electrode material for a nonaqueous secondary battery according to [1], wherein the amount of mercury intrusion A is 0.001 mL / g or more and 0.5 mL / g or less. [3] The raw material for a negative electrode material for a non-aqueous secondary battery according to [1] or [2], wherein the amount of mercury discharged B is 0.0005 mL / g or more and 0.5 mL / g or less. [4] Tap density is 0.7 g / cm 3 More than 1.4g / cm 3 The raw material for a negative electrode material for a non-aqueous secondary battery according to any one of [1] to [3] below. [5] A negative electrode material for a non-aqueous secondary battery, comprising the negative electrode material for a non-aqueous secondary battery according to any one of [1] to [4]. [6] The nonaqueous secondary battery negative electrode material according to [5], wherein the interplanar spacing (d002) obtained by X-ray diffraction is 0.34 nm or less, and the crystallite size in the c-axis direction (Lc) is 90 nm or more. [7] The negative electrode material for a nonaqueous secondary battery according to [5] or [6], wherein the Raman R1 value calculated from the following formula α is 0.15 or more and 1.00 or less. Formula α: [Raman R value] = [1360 cm in Raman spectrum analysis]-1 Nearby peak P B Intensity I B ] / [1580cm -1 Nearby peak P A Intensity I A ] [8] A non-aqueous secondary battery using the negative electrode material according to any one of [5] to [7]. Effect of the Invention
[0009] According to the present invention, there are provided a raw material for a negative electrode material for a non-aqueous secondary battery, which can provide a non-aqueous secondary battery that has a high capacity, excellent rapid charging characteristics, and small plate swelling after cycling, and a negative electrode material for a non-aqueous secondary battery and a non-aqueous secondary battery that include the same. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a graph showing the relationship between the amount of mercury discharged / the amount of mercury injected (B / A) and cycle swelling in Examples 1 to 2 and Comparative Examples 1 to 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present invention will be described in detail below, but the present invention is not limited to the following description, and can be modified as desired without departing from the gist of the present invention. In the present invention, when a numerical value or physical property value is enclosed before and after "~", the value before and after the "~" is included.
[0012] [Raw material for negative electrode material for non-aqueous secondary batteries] The negative electrode material raw material for a non-aqueous secondary battery according to one embodiment of the present invention (hereinafter, may be referred to as the "negative electrode material raw material of the present invention") contains graphite, and when the amount of mercury injected (mL / g) measured by mercury intrusion porosimetry is A and the amount of mercury discharged (mL / g) is B, the ratio of the amount of mercury discharged / the amount of mercury intrusion (B / A) × 100 is 45% or more. The amount of mercury discharged / the amount of mercury intrusion (B / A) is an index of the complexity of the particle structure of the raw material for the negative electrode, and the complexity of the particle structure leads to the magnitude of the residual stress in the particle, and the magnitude of the residual stress in the particle may lead to the tendency of particle expansion to occur during the charge / discharge cycle of the negative electrode material using this raw material. Therefore, the amount of mercury discharged / the amount of mercury intrusion (B / A) x 100 is usually 45% or more, more preferably 50% or more, even more preferably 55% or more, particularly preferably 60% or more, and most preferably 63% or more. The upper limit of mercury elution amount / mercury intrusion amount (B / A) × 100 is not particularly limited, but the less complex the intraparticle structure is (i.e., the simpler the intraparticle structure is), the lower the particle sphericity tends to be, and as the particle sphericity decreases, the lithium ion diffusibility in a negative electrode using a negative electrode material made from this raw material decreases, which can have a significant adverse effect on load characteristics such as rapid charging performance, so the upper limit is preferably 95% or less, more preferably 90% or less, even more preferably 85% or less, and most preferably 80% or less. The amount of mercury intrusion (mL / g) A is not particularly limited, but a small A means a small amount of intraparticle pores, and a small amount of intraparticle pores may lead to a decrease in load characteristics such as input / output characteristics of the negative electrode material using this raw material. Therefore, the amount of mercury intrusion (mL / g) A is preferably 0.001 mL / g or more, more preferably 0.003 mL / g or more, even more preferably 0.005 mL / g or more, particularly preferably 0.01 mL / g or more, and most preferably 0.03 mL / g or more. As for the upper limit of the amount of mercury intrusion (mL / g) A, a large A means a large amount of intraparticle pores, and a large amount of intraparticle pores may lead to a decrease in the efficiency of slurry preparation and electrode drying efficiency due to a decrease in the bulk density of the negative electrode material using this raw material, so it is preferably 1.0 mL / g or less, more preferably 0.8 mL / g or less, even more preferably 0.6 mL / g or less, particularly preferably 0.4 mL / g or less, and most preferably 0.3 mL / g or less. The amount of mercury discharged (mL / g) B is not particularly limited, but a small B reflects a small amount of intraparticle pores or a complex intraparticle structure, the former of which may lead to a decrease in load characteristics such as input / output characteristics of the negative electrode material using this raw material, and the latter of which reflects a large residual stress in the particles, and a large residual stress in the particles may lead to concerns about particle expansion accompanying the charge / discharge cycle of the negative electrode material using this raw material. Therefore, the amount of mercury discharged (mL / g) B is preferably 0.001 mL / g or more, more preferably 0.005 mL / g or more, even more preferably 0.010 mL / g or more, particularly preferably 0.040 mL / g or more, and most preferably 0.065 mL / g or more. The upper limit of the amount of mercury escape (mL / g) B is preferably 1.0 mL / g or less, more preferably 0.6 mL / g or less, even more preferably 0.4 mL / g or less, particularly preferably 0.2 mL / g or less, and most preferably 0.1 mL / g or less, since a large B means that the amount of mercury injected (mL / g) A immediately before measuring B is large, and if A is too large there is the above-mentioned concern. The above-mentioned raw materials for the negative electrode material are preferable because, when contained in the negative electrode material, swelling of the electrode plate after cycles (cycle swelling) accompanying the charge and discharge of the secondary battery can be suppressed.
[0013] The negative electrode material for non-aqueous secondary batteries and the negative electrode material for non-aqueous secondary batteries according to the present embodiment provide a non-aqueous secondary battery having a high capacity, excellent suppression of cycle swelling, and excellent rapid charging performance. Although the reason why the present invention provides such an effect is not clear, the following reasons are considered.
[0014] In the negative electrode material of this embodiment, the ratio of the amount of mercury discharged / the amount of mercury intrusion (B / A) is an index of the complexity of the intraparticle structure, and the smaller the B / A value, the more complex the intraparticle structure. The complexity of the intraparticle structure is linked to the magnitude of residual stress within the particle, and the magnitude of residual stress within the particle determines the likelihood of particle expansion occurring during charge / discharge cycles of the negative electrode material using this negative electrode material. By setting the value of B / A × 100 to 45% or more, the complexity of the particle structure can be kept below a certain level, and residual stress within the particles can be suppressed, making it possible to suppress particle expansion that occurs during charge-discharge cycles of anode materials using this anode material raw material, and it is believed that this will be effective in suppressing cycle swelling of the anode.
[0015] Furthermore, by maintaining the value of B / A×100 at 63% or more, it is possible to further improve the rapid charging performance while effectively suppressing cycle swelling of the negative electrode. This is thought to be because the diffusion of lithium ions in the negative electrode is promoted, the lithium ion concentration gradient in the negative electrode becomes gentler, and the concentration overpotential is suppressed under conditions of use where material diffusion is rate-limiting, such as rapid charging.
[0016] [Physical Properties] The negative electrode material according to one embodiment of the present invention satisfies (B / A)×100 described below. <Amount of mercury injected and amount of mercury discharged> In the negative electrode raw material of the present invention, when the amount of mercury injected (mL / g) measured by mercury intrusion porosimetry is A and the amount of mercury released (mL / g) is B, the ratio of the amount of mercury released / the amount of mercury injected (B / A)×100 is 45% or more.
[0017] A mercury porosimeter (Autopore 9520: manufactured by Micromeritics) can be used as the device for the mercury porosimetry. A sample (negative electrode raw material) is weighed to a value of about 0.2 g, sealed in a powder cell, and degassed for 10 minutes at room temperature under vacuum (50 μmHg or less) to perform pretreatment. Subsequently, the pressure is reduced to 4 psia (about 28 kPa) and mercury is introduced into the cell, and the pressure is increased stepwise from 4 psia (about 28 kPa) to 40,000 psia (about 280 MPa), and then decreased to 25 psia (about 170 kPa). The number of steps during pressure increase is 42 or more, and the number of steps during pressure decrease is 39 or more, and after a 10-second equilibration time at each step, the amount of mercury intrusion is measured. The pore distribution is calculated from the mercury intrusion curve obtained in this way using the Washburn formula. The calculations are based on a surface tension (γ) of mercury of 485 dyne / cm and a contact angle (ψ) of 140°. The average pore diameter is defined as the pore diameter when the cumulative pore volume is 50%. From the mercury intrusion behavior and mercury exit behavior obtained in this way, the amount of mercury intrusion (A) and the amount of mercury exit (B) were calculated as follows. Amount of mercury injected (A) = Cumulative pore volume of 0.01 μm to 0.6 μm on the injection side (mL / g) Amount of mercury withdrawn (B) = Amount of mercury withdrawn up to 25 psia (approximately 170 kPa) on the withdrawal side (mL / g)
[0018] Moreover, it is preferable that the raw material for the negative electrode material according to one embodiment of the present invention satisfies the following properties.
[0019] (Circularity) In the negative electrode material according to one embodiment of the present invention, the circularity determined by flow-type particle image analysis is preferably 0.88 or more, more preferably 0.90 or more, even more preferably 0.91 or more, particularly preferably 0.92 or more, and most preferably 0.93 or more. Such graphite with a high circularity is preferable because the degree of tortuosity of Li ion diffusion in the negative electrode material produced using it is reduced, the movement of the electrolyte in the interparticle voids becomes smooth, and the rapid charging characteristics can be improved. On the other hand, since the theoretical upper limit of this circularity is 1, it is usually less than 1, preferably 0.99 or less, more preferably 0.98 or less, and even more preferably 0.97 or less. From the viewpoint of ensuring contact between the obtained negative electrode materials and improving cycle characteristics, it is preferable that it is below the above upper limit.
[0020] Circularity was measured using a flow particle image analyzer (FPIA-2000, manufactured by Toa Medical Electronics Co., Ltd.). It is determined by measuring the particle size distribution based on the circle equivalent diameter and calculating the average circularity. Circularity is defined by the following formula, with a circularity of 1 being a theoretical perfect sphere. [Circularity] = [Perimeter of a circle with the same area as the projected shape of a particle] / [Actual perimeter of the projected shape of a particle]
[0021] In measuring the circularity, ion-exchanged water is used as the dispersion medium, and polyoxyethylene (20) monolaurate is used as the surfactant. The equivalent circle diameter is the diameter of a circle (equivalent circle) that has the same projected area as the photographed particle image, and the circularity is the ratio of the perimeter of the equivalent circle as the numerator to the perimeter of the photographed particle projected image as the denominator. The circularities of particles with measured equivalent diameters in the range of 1.5 to 40 μm are averaged to obtain the circularity.
[0022] (Tap density) The tap density of the negative electrode material is preferably 0.60 g / cm 3 More preferably, it is 0.70 g / cm 3 More preferably, it is 0.80 g / cm 3 More preferably, it is 0.855 / cm 3More preferably, it is 0.90 g / cm 3 or more, whereas the usual 3 or less, preferably 1.30 g / cm 3 More preferably, it is 1.20 g / cm or less. 3 The following is the result. The tap density is measured using a powder density measuring instrument, Tap Denser KYT-3000, manufactured by Seishin Enterprise Co., Ltd. Specifically, a sample is dropped into a 20 cc tap cell, the cell is filled to capacity, and then tapping is performed 1000 times with a stroke length of 10 mm, and the density at that time is defined as the tap density.
[0023] (Volume-based average particle size) The volume-based average particle size (D50) of the negative electrode material raw material is not particularly limited, but is usually 1 μm or more, preferably 3 μm or more, more preferably 5 μm or more, even more preferably 8 μm or more, and particularly preferably 10 μm or more, and is usually 50 μm or less, preferably 40 μm or less, more preferably 30 μm or less, even more preferably 20 μm or less, particularly preferably 16 μm or less, and most preferably 14 μm or less. The average particle diameter (d50) is defined as a value measured by suspending 0.01 g of the composite particles in 10 mL of a 0.2 wt % aqueous solution of polyoxyethylene sorbitan monolaurate (an example of which is Tween 20 (registered trademark)) which is a surfactant, introducing the resultant suspension as a measurement sample into a commercially available laser diffraction / scattering type particle size distribution measurement device (e.g., LA-920 manufactured by HORIBA), irradiating the measurement sample with 28 kHz ultrasonic waves at an output of 60 W for 1 minute, and then measuring the volume-based median diameter in the measurement device.
[0024] (BET specific surface area) The BET specific surface area of the negative electrode material is not particularly limited, but is usually 1.0 m 2 / g or more, preferably 1.5m 2 / g or more, more preferably 2.0m 2 / g or more, more preferably 3.0m 2 / g or more, and particularly preferably 4.5m2 / g or more, and most preferably 5.0m 2 / g or more. Also, usually, 30.0m 2 / g or less, preferably 25.0m 2 / g or less, and more preferably 20.0m 2 / g or less, and more preferably 16.0m 2 / g or less, and particularly preferably 13.0m 2 / g or less, and particularly preferably 12.0m 2 / g or less. The BET specific surface area (SA) can be measured using a Maxorb manufactured by Mountec Co., Ltd. Specifically, the sample is pre-dried under reduced pressure at 100°C for 3 hours under a nitrogen flow, then cooled to liquid nitrogen temperature, and the BET single-point method using nitrogen adsorption with a gas flow method is used to measure the SA, using a nitrogen-helium mixed gas precisely adjusted so that the relative pressure of nitrogen to atmospheric pressure is 0.3.
[0025] [Non-aqueous secondary battery negative electrode material] The negative electrode material for a non-aqueous secondary battery of the present invention contains the above-mentioned raw material for the negative electrode material for a non-aqueous secondary battery of the present invention. [Physical Properties] (Raman R1 value) The Raman R1 value in this specification is the Raman R1 value at 1580 cm in the Raman spectrum obtained by Raman spectroscopy for the negative electrode material, as shown in the following formula α. -1 Nearby peak P A Intensity I A And, 1360cm -1 Nearby peak P B Intensity I B The intensity ratio (I B / I A ) is defined as "1580cm -1 "Near" means 1580~1620cm -1 The range is set to "1360cm -1 "Around 1350~1370cm" -1 Refers to the range. The Raman R1 value of the negative electrode material, represented by the following formula α, is not particularly limited, but is preferably 0.10 to 1.00. The Raman R value is more preferably 0.15 or more, even more preferably 0.20 or more, and particularly preferably 0.25 or more, while being more preferably 0.80 or less, and even more preferably 0.60 or less. Formula α: Raman R value = (1360 cm in Raman spectrum analysis) -1 Nearby peak P B Intensity I B ) / (1580cm -1 Nearby peak P A Intensity I A )
[0026] <Raman characteristics of negative electrode material (Raman R1 value, Raman full width at half maximum Δν B (cm -1 ), Raman R2 value, Raman R3 value) (Raman R1 value) As described above, the Raman R1 value in this specification is the value at 1580 cm in the Raman spectrum obtained by Raman spectroscopy for the negative electrode material, as shown in the following formula α. -1 Nearby peak P A Intensity I A And, 1360cm -1 Nearby peak P B Intensity I B The intensity ratio (I B / I A ) is defined as "1580cm -1 "Around 1580~1620cm" -1 The range is set to "1360cm -1 "Around 1350~1370cm" -1 Refers to the range. Formula α: [Raman R value] = [1360 cm in Raman spectrum analysis] -1 Nearby peak P B Intensity I B ] / [1580cm -1 Nearby peak P A Intensity I A ]
[0027] The Raman full width at half maximum Δν B (cm -1 ) is the Raman spectrum of the negative electrode material obtained by Raman spectroscopy at 1360 cm -1 Nearby peak P B The full width at half maximum of 1360 cm -1 "Around 1350~1370cm" -1 Refers to the range.
[0028] The Raman R2 value in this specification is the Raman R2 value at 1580 cm in the Raman spectrum obtained by Raman spectroscopy for the negative electrode material, as shown in the following formula β. -1 Nearby peak P A Intensity I A And, 1580cm -1 Nearby peak P A and 1360cm -1 Nearby peak P B Intensity of the valley (minimum) between I C The intensity ratio (I C / I A ) is defined as "1580cm -1 "Near" means 1580~1620cm -1 The range is set to "1360cm -1 "Around 1350~1370cm" -1 Refers to the range. Formula β: [Raman R value] = [1580 cm in Raman spectrum analysis] -1 Nearby peak P A and 1360cm -1 Nearby peak P B Intensity of the valley (minimum) between I C ] / [1580cm -1 Nearby peak P A Intensity I A ]
[0029] In one embodiment of the present invention, the Raman R3 value is calculated by the following formula γ, which is calculated by Raman spectroscopy for the negative electrode material at 1360 cm -1 Nearby peak P B Intensity I BAnd, 1580cm -1 Nearby peak P A and 1360cm -1 Nearby peak P B Between Intensity of the valley (minimum) I C The intensity ratio (I C / I B ) is defined as "1580cm -1 "Around 1580~1620cm" -1 The range is set to "1360cm -1 "Around 1350~1370cm" -1 Refers to the range. Formula γ: [Raman R3 value] = [1580 cm in Raman spectrum analysis] -1 Nearby peak P A and 1360cm -1 Nearby peak P B Intensity of the valley (minimum) between I C ] / [1360cm -1 Nearby peak P B Intensity I B ]
[0030] The Raman R1 value of the negative electrode material according to one embodiment of the present invention is usually 0.15 or more, preferably 0.20 or more, more preferably 0.25 or more, even more preferably 0.30 or more, particularly preferably 0.32 or more, and most preferably 0.35 or more. Also, it is usually 1.00 or less, preferably 0.80 or less, more preferably 0.70 or less, even more preferably 0.65 or less, and particularly preferably 0.50 or less.
[0031] The Raman full width at half maximum (Δν B ) is usually 65cm -1 More than 70cm, preferably 70cm -1 More than 80cm, preferably 80cm -1 More than 85cm, more preferably 85cm -1 More than 90cm, especially preferred -1 More than 100cm, most preferably 100cm -1 More than that. Also, normally 400cm -1 Less than 300cm, preferably -1Less than or equal to 250 cm, more preferably -1 Less than 200cm, more preferably -1 Below 170cm, especially preferred -1 Below 145cm, most preferably -1 The following is the result.
[0032] The Raman R2 value of the negative electrode material according to one embodiment of the present invention is preferably 0.03 or more, more preferably 0.05 or more, even more preferably 0.07 or more, particularly preferably 0.09 or more, and most preferably 0.11 or more. Also, it is usually 0.60 or less, preferably 0.40 or less, more preferably 0.30 or less, even more preferably 0.25 or less, and particularly preferably 0.22 or less.
[0033] These Raman characteristics are indices of the graphite crystallinity of the anode material surface, and the larger these values are, the lower the graphite crystallinity of the anode material surface (the more amorphous it is). B / I A ) is influenced not only by the degree of graphitization (the perfection of the graphite structure) but also by the ratio of edges and crystal boundaries on the graphite crystal surface, and the larger the Raman R1 value, the lower the degree of graphitization and the higher the ratio of edges and crystal boundaries tends to be. For this reason, the Raman R1 value can be large not only when part of the negative electrode material surface contains amorphous carbonaceous matter, but also when the edge ratio increases due to graphite being crushed in a fractured manner, etc. On the other hand, the Raman full width at half maximum (Δν B ) is relatively less affected by the ratio of edges and crystal boundaries on the graphite crystal surface, and tends to be more affected by the degree of graphitization (the perfection of the graphite structure). For this reason, the Raman full width at half maximum (Δν B ) tends to increase when part of the negative electrode surface has amorphous carbon, but the change tends to be relatively small when the edge ratio is increased by grinding, etc. -1 Nearby peak P A and 1360cm -1 Nearby peak P B Intensity of the valley (minimum) between I CIt is said that this is due to defects in the graphite crystal structure and the SP3 nature of the amorphous carbon structure, and the Raman R2 value (I C / I A ) and Raman R3 value (I C / I B ) tends to reflect the effect of the degree of graphitization (the perfection of the local graphite structure). For this reason, the Raman R2 value (I C / I A ) and Raman R3 value (I C / I B ) tends to increase when part of the surface of the negative electrode material contains amorphous carbonaceous material, but the change tends to be relatively small when the edge ratio is increased by grinding or the like.
[0034] The fact that the parameter values of these Raman characteristics are equal to or greater than the lower limit above indicates that the amorphousness of the anode material surface is within an appropriate range, and the low-temperature input / output characteristics tend to improve as Li ions are more easily inserted and removed. On the other hand, if the parameter values of these Raman characteristics are equal to or less than the upper limit above, the effect of the irreversible capacity of the highly amorphous carbon increases and side reactions with the electrolyte occur. This suppresses an increase in the amount of gas generated and reduces a decrease in the initial charge / discharge efficiency of the lithium ion secondary battery, and tends to improve the battery capacity.
[0035] The Raman spectrum is measured by a Raman spectrometer. Specifically, the particles to be measured are loaded into a measurement cell by gravity, and the measurement cell is irradiated with argon ion laser light while the measurement cell is rotated in a plane perpendicular to the laser light. Argon ion laser light wavelength: 514.5nm Laser power on sample: 25mW Resolution: 4cm -1 Measurement range: 1100cm -1 ~1730cm -1 Peak intensity measurement, peak full width at half maximum measurement: background processing, smoothing processing (convolution 5 points by simple average)
[0036] <BET Specific Surface Area (SA)> The negative electrode material according to an embodiment of the present invention has a specific surface area (SA) by the BET method of preferably 0.5 m 2 / g or more, more preferably 1.0 m 2 / g or more, still more preferably 1.2 m 2 / g or more, particularly preferably 1.5 m 2 / g or more, most preferably 1.8 m 2 / g or more, while preferably 10.0 m 2 / g or less, more preferably 6.5 m 2 / g or less, still more preferably 5.0 m 2 / g or less, particularly preferably 4.0 m 2 / g or less, most preferably 3.0 m 2 / g or less. When SA is equal to or greater than the above lower limit value, a site for Li ions to enter and exit is secured, and the rapid charge and discharge characteristics of the lithium ion secondary battery tend to be good. On the other hand, when SA is equal to or less than the above upper limit value, the activity of the active material with respect to the electrolyte is not excessive, side reactions with the electrolyte are suppressed, a decrease in the initial charge and discharge efficiency of the battery and an increase in the amount of gas generation are prevented, and the battery capacity tends to improve. The BET specific surface area (SA) is measured by the same method as the method described for the negative electrode material raw material.
[0037] <Tap Density> The negative electrode material according to an embodiment of the present invention has a tap density (g / cm 3 ) of preferably 0.60 g / cm 3 or more, more preferably 0.80 g / cm 3 or more, still more preferably 1.00 g / cm 3 or more, particularly preferably 1.10 g / cm 3 or more, most preferably 1.15 g or more, while preferably 1.40 g / cm 3 or less, more preferably 1.35 g / cm 3 or less, still more preferably 1.30 g / cm 3 or less, particularly preferably 1.24 g / cm 3The tap density is the lower limit or more, which is preferable from the viewpoint that the processability such as streaking during electrode plate preparation is improved, the packing property of the negative electrode material layer is improved, so that the rolling property is good and a high-density negative electrode sheet is easily formed, and high density is possible, and when it is made into an electrode body, the degree of curvature of the Li ion migration path is reduced, and the shape of the interparticle voids is regularized, so that the movement of the electrolyte is smooth and the rapid charge / discharge characteristics are improved, and the tap density is the upper limit or less, which is preferable from the viewpoint that the particles do not become too hard because there is a moderate space on the surface and inside of the particles, and the electrode pressability is excellent, and the rapid charge / discharge characteristics are excellent. The tap density is measured by the same method as that described in the negative electrode material raw material.
[0038] <Interplanar spacing (d002) and crystallite size (Lc)> In the negative electrode material according to one embodiment of the present invention, the crystallinity (degree of graphitization) is preferably such that the interplanar spacing (d002) of the (002) plane determined by the wide-angle X-ray diffraction method according to the Gakushin method is 0.340 nm or less, and the size of the crystallite in the c-axis direction (Lc) is 90 nm or more. The d002 value is more preferably 0.338 nm or less, and even more preferably 0.337 nm or less. Furthermore, Lc is more preferably 95 nm or more, and even more preferably 100 nm or more. When d002 and Lc are in the above ranges, the discharge capacity is increased, which is preferable from the viewpoint of increasing the capacity of the battery.
[0039] <Circularity> In the negative electrode material according to one embodiment of the present invention, the circularity determined by flow-type particle image analysis is preferably 0.88 or more, more preferably 0.90 or more, even more preferably 0.91 or more, particularly preferably 0.92 or more, and most preferably 0.93 or more. In such a negative electrode material with a high circularity, the degree of tortuosity of Li ion diffusion is reduced, the movement of the electrolyte in the interparticle voids is smooth, and rapid charge / discharge characteristics can be improved, which is preferable. On the other hand, since the theoretical upper limit of this circularity is 1, it is usually less than 1, preferably 0.99 or less, more preferably 0.98 or less, and even more preferably 0.97 or less. From the viewpoint of ensuring contact between the obtained negative electrode materials and improving cycle characteristics, it is preferable that it is below the above upper limit. The circularity is determined by the same method as that described in the negative electrode material raw material.
[0040] <Volume-based average particle size (average particle size d50)> In the negative electrode material according to one embodiment of the present invention, the volume-based average particle diameter (also referred to as "average particle diameter d50") is preferably 1 μm or more, more preferably 3 μm or more, even more preferably 4 μm or more, particularly preferably 5 μm or more, and most preferably 8 μm or more. Also, it is preferably 50 μm or less, more preferably 40 μm or less, even more preferably 30 μm or less, particularly preferably 20 μm or less, and most preferably 14 μm or less. When the value of d50 is equal to or more than the above lower limit, there is a tendency to easily prevent an increase in irreversible capacity and a loss of initial battery capacity, while when the value of d50 is equal to or less than the above upper limit, there is a tendency to prevent process problems such as streaking during slurry application, and to improve rapid charge / discharge characteristics and low-temperature input / output characteristics. The volume-based average particle diameter is determined by the same method as that described for the raw material of the negative electrode material.
[0041] [Manufacturing method] The method for producing a raw material for a negative electrode material for a non-aqueous secondary battery according to one embodiment of the present invention is not particularly limited as long as it contains graphite and can produce a graphite such that the mercury elution amount / mercury elution amount (B / A)×100 satisfies 45% or more, where the mercury elution amount (mL / g) measured by mercury porosimetry is A and the mercury elution amount (mL / g) is B. For example, the graphite can be produced by pressurizing spherical graphite that has been subjected to a spheroidizing treatment. Examples of the pressurizing treatment include anisotropic and isotropic pressurizing treatments, but isotropic pressurizing treatment is preferred from the viewpoint of controlling the mercury elution amount / mercury elution amount (B / A) within a specific range. In addition, the conditions for the pressurizing treatment are not particularly limited, but by treating at 50 MPa or more and 300 MPa or less, the mercury elution amount / mercury elution amount (B / A) can be controlled within a specific range. The conditions of the pressure treatment are preferably 100 MPa or more, more preferably 120 MPa or more, even more preferably 140 MPa or more, particularly preferably 160 MPa or more, most preferably 180 MPa or more, and also preferably 280 MPa or less, more preferably 260 MPa or less, even more preferably 240 MPa or less, particularly preferably 230 MPa or less, and most preferably 220 MPa or less, from the viewpoint of controlling the mercury discharge amount / mercury intrusion amount (B / A) within a specific range. Specifically, the above-mentioned production method is, for example, pulverizing natural graphite, mixing a granulating agent with the pulverized natural graphite, performing a spheroidizing treatment, and further removing the granulating agent by a heat treatment to obtain spheroidized graphite. The obtained spheroidized graphite is pressurized, and the obtained molded product is crushed and classified, whereby a raw material for a negative electrode material for a non-aqueous secondary battery in which the mercury discharge amount / mercury intrusion amount (B / A) is controlled within a specific range can be produced. In addition, the method for producing the negative electrode material for non-aqueous secondary batteries according to one embodiment of the present invention is not particularly limited, but it can be produced by mixing the raw material for the negative electrode material for non-aqueous secondary batteries according to one embodiment of the present invention with an amorphous carbon precursor (raw material of amorphous carbon) and firing it. Specifically, it is possible to adjust the pore volume by pressure treatment as spherical graphite and achieve a specific range of mercury withdrawal amount / mercury intrusion amount, and it is preferable to use an amorphous carbon precursor with low ash content, metal impurity content, quinoline insoluble content (Qi), etc., suitable for the development of carbon structure, and to fire it in an inert atmosphere at a moderate firing temperature.
[0042] <Graphite> The negative electrode material according to one embodiment of the present invention includes graphite. The graphite used to manufacture the negative electrode material according to one embodiment of the present invention preferably has the following types and physical properties. The measurement conditions and definitions of the physical properties of graphite are the same as those described for the negative electrode material described above, unless otherwise specified.
[0043] The type of graphite is not particularly limited as long as it can absorb and release lithium ions, and may be either natural graphite or artificial graphite. Natural graphite may be any of flake graphite, lump graphite, and earthy graphite, but graphite with few impurities is preferable, and it is preferable to use it after performing a known purification process as necessary. Examples of artificial graphite include coal tar pitch, coal-based heavy oil, atmospheric residual oil, petroleum-based heavy oil, aromatic hydrocarbons, nitrogen-containing cyclic compounds, sulfur-containing cyclic compounds, polyphenylene, polyvinyl chloride, polyvinyl alcohol, polyacrylonitrile, polyvinyl butyral, natural polymers, polyphenylene silicide, polyphenylene oxide, furfuryl alcohol resin, phenol-formaldehyde resin, and imide resin, which are graphitized by baking at a temperature usually in the range of 2500°C or higher and usually 3200°C or lower. In this case, silicon-containing compounds and boron-containing compounds can also be used as graphitization catalysts.
[0044] The crystallinity (degree of graphitization) of graphite is usually such that the interplanar spacing (d002) of the (002) plane measured by wide-angle X-ray diffraction method is 0.335 nm or more and less than 0.340 nm. The d002 value is preferably 0.338 nm or less, more preferably 0.337 nm or less, and even more preferably 0.336 nm or less.
[0045] From the viewpoint of rapid charge and discharge characteristics, the shape of the graphite is preferably spherical graphite (spheroidized graphite). As a method for spheroidizing graphite particles, spherical graphite particles can be manufactured by performing a spheroidization process using a known technique. For example, the spheroidization process can be performed using an apparatus that repeatedly applies mechanical actions such as compression, friction, shear force, etc., including particle interactions, mainly impact force, to particles. Specifically, the apparatus used for the spheroidization process is preferably an apparatus having a rotor with many blades installed inside a casing, which rotates at high speed to apply mechanical actions such as impact compression, friction, shear force, etc. to the carbon material introduced inside, thereby performing surface treatment. In addition, it is preferable that the apparatus has a mechanism for repeatedly applying mechanical actions by circulating graphite particles. Specific examples of the apparatus include a hybridization system (manufactured by Nara Machinery Works), a Cryptron (manufactured by EarthTechnica), a CF mill (manufactured by Ube Industries), a Mechanofusion system (manufactured by Hosokawa Micron Corporation), and a Theta Composer (manufactured by Tokuju Machinery Works). Among these, the hybridization system manufactured by Nara Machinery Works is preferred. For example, when the above-mentioned apparatus is used for treatment, the circumferential speed of the rotating rotor is not particularly limited, but is preferably 30 m / sec to 100 m / sec, more preferably 40 m / sec to 100 m / sec, and even more preferably 50 m / sec to 100 m / sec. In addition, the treatment can be performed by simply passing the carbonaceous material through the apparatus, but it is preferable to circulate or retain the material in the apparatus for 30 seconds or more, and more preferably to circulate or retain the material in the apparatus for 1 minute or more. In addition, spherical graphite obtained by granulating a plurality of pieces of scaly or flaky graphite, graphite such as ground graphite fine powder, and a granulating agent by the method described in Patent Document 4 may be used.
[0046] (Circularity) The graphite used in the raw material for the negative electrode material according to one embodiment of the present invention has a circularity of preferably 0.88 or more, more preferably 0.90 or more, even more preferably 0.91 or more, particularly preferably 0.92 or more, and most preferably 0.93 or more, as determined by flow particle image analysis. When the graphite has such a high circularity, the degree of tortuosity of Li ion diffusion in the negative electrode material produced using it is reduced, and the electrolyte migration in the interparticle voids is improved. This is preferable because the movement becomes smoother and the rapid charge / discharge characteristics can be improved. On the other hand, since the theoretical upper limit of the circularity is 1, it is usually less than 1, preferably 0.99 or less, more preferably 0.98 or less, and further preferably 0.97 or less. From the viewpoint of ensuring contact between the obtained negative electrode materials and improving cycle characteristics, it is preferable that the circularity is equal to or less than the upper limit.
[0047] (Tap density) The tap density of the graphite is preferably 0.60 g / cm 3 More preferably, it is 0.70 g / cm 3 More preferably, it is 0.80 g / cm 3 More preferably, it is 0.855 / cm 3 More preferably, it is 0.90 g / cm 3 or more, whereas the usual 3 and preferably 1.30 g / cm 3 More preferably, it is 1.20 g / cm or less. 3 The following is the result.
[0048] (Volume-based average particle size) The volume-based average particle size (D50) of graphite is not particularly limited, but is usually 1 μm or more, preferably 3 μm or more, and more preferably 5 μm or more, and is usually 50 μm or less, preferably 40 μm or less, and more preferably 30 μm or less.
[0049] (BET specific surface area) The BET specific surface area of graphite is not particularly limited, but is usually 1.0 m 2 / g or more, preferably 1.5m 2 / g or more, more preferably 2.0m 2 / g or more, more preferably 3.0m 2 / g or more, and particularly preferably 4.5m 2 / g or more, and most preferably 5.0m 2 / g or more. Also, usually, 30.0m 2 / g or less, preferably 25.0m 2 / g or less, and more preferably 20.0m 2 / g or less.
[0050] (Raman R1 value) The Raman R1 value of graphite, represented by the following formula α, is not particularly limited, but is preferably 0.10 or more and 1.00 or less. The Raman R value is more preferably 0.15 or more, even more preferably 0.20 or more, and particularly preferably 0.25 or more, while more preferably 0.80 or less, and even more preferably 0.60 or less. Formula α: Raman R value = (1360 cm in Raman spectrum analysis) -1 Nearby peak P B Intensity I B ) / (1580cm -1 Nearby peak P A Intensity I A )
[0051] <Graphite pressure treatment> The manufacturing method of the negative electrode material according to one embodiment of the present invention preferably includes a step of pressurizing graphite. The method of pressurizing graphite is not particularly limited as long as it is a method capable of applying pressure, and examples of the method include placing the graphite as a raw material in a container such as a rubber mold, and performing hydrostatic isotropic pressurizing treatment using water as a pressurizing medium, and air pressure isotropic pressurizing treatment using a gas such as air as a pressurizing medium. Alternatively, the graphite as a raw material may be filled in a mold, and pressurized in a certain direction by a uniaxial press.
[0052] The pressure of the pressure medium for the graphite pressure treatment is preferably in the range of 5 to 400 MPa, more preferably in the range of 30 to 350 MPa, and even more preferably in the range of 50 to 300 MPa. If the pressure is equal to or higher than the lower limit, the pore volume can be made smaller. If the pressure is equal to or lower than the upper limit, the increase in the specific surface area of the resulting negative electrode material tends to be easily suppressed.
[0053] <Compositing of amorphous carbon with negative electrode raw materials> The negative electrode material according to one embodiment of the present invention preferably contains graphite having amorphous carbon on at least a part of the surface. The amorphous carbon composite treatment is carried out by mixing the above-mentioned graphite-containing negative electrode material raw material and an amorphous carbon precursor (amorphous carbon raw material) and baking the mixture. By carrying out the amorphous carbon composite formation of the negative electrode material under appropriate conditions, it becomes easier to control the cumulative pore volume within the above-mentioned range.
[0054] The amorphous carbon precursor is not particularly limited, but includes organic substances such as tar, pitch, aromatic hydrocarbons such as naphthalene, anthracene and their derivatives, phenolic resins, and thermoplastic polymers such as polyvinyl alcohol. These organic precursors may be used alone or in combination of two or more. Among these, tar, pitch, and aromatic hydrocarbons are preferred from the viewpoint of facilitating the development of a carbon structure.
[0055] The ash content of the amorphous carbon precursor is preferably 1% by weight or less, more preferably 0.5% by weight or less, and even more preferably 0.1% by weight or less, based on the total weight of the amorphous carbon precursor. The lower limit of the ash content is usually 0.1 ppm by weight or more. When the ash content of the amorphous carbon precursor is within the above range, the thermal properties are good.
[0056] The amount of metal impurities contained in the amorphous carbon precursor in the present invention is defined as the value obtained by dividing the residual carbon ratio by the total content of Fe, Al, Si, and Ca relative to the total weight of the amorphous carbon precursor. It is preferably 1000 ppm by weight or less, more preferably 400 ppm by weight or less, even more preferably 100 ppm by weight or less, particularly preferably 50 ppm by weight or less, and usually 0.1 ppm by weight or more, relative to the total weight of the amorphous carbon precursor. When the amount of metal impurities contained in the amorphous carbon precursor is within the above range, the thermal properties are good.
[0057] The quinoline insoluble matter (Qi) contained in the amorphous carbon precursor is preferably 5 wt % or less, more preferably 2 wt % or less, even more preferably 1 wt % or less, particularly preferably 0.5 wt % or less, and most preferably 0.1 wt % or less, based on the total weight of the amorphous carbon precursor. When the quinoline insoluble matter (Qi) contained in the amorphous carbon precursor is within the above range, the thermal properties are good.
[0058] After mixing the graphite and the amorphous carbon precursor, the mixture is fired. The firing temperature is preferably 950°C or higher, more preferably 1000°C or higher, even more preferably 1050°C or higher, particularly preferably 1100°C or higher, and most preferably 1150°C or higher. On the other hand, it is preferably 2000°C or lower, more preferably 1800°C or lower, even more preferably 1600°C or lower, and particularly preferably 1500°C or lower. The firing time is preferably 0.5 hours or higher, more preferably 1 hour or higher, while it is preferably 1000 hours or lower, more preferably 500 hours or lower, and even more preferably 100 hours or lower. When the firing temperature and time are within the above ranges, the thermal properties are good.
[0059] The atmosphere during firing is preferably an inert atmosphere. Specifically, there are a method of reducing the oxygen concentration by circulating an inert gas such as nitrogen or argon, a method of discharging oxygen outside the system by a decompression treatment and restoring the pressure with nitrogen or argon, and a method of reducing the oxygen contained in the furnace atmosphere by filling the periphery of the product with a sacrificial material such as coke breeze. The oxygen concentration in the system can be controlled by the amount and time of the inert gas flow, the degree of the decompression treatment, the filling conditions of the sacrificial material, etc. The oxygen concentration (volume concentration) is preferably 3% or less, more preferably 1% or less, even more preferably 1000 ppm or less, particularly preferably 500 ppm or less, and most preferably 100 ppm or less. If the oxygen concentration exceeds the above range, the development of the carbon structure of the amorphous carbonaceous material is inhibited, and favorable thermal properties tend not to be obtained.
[0060] When the amorphous carbon precursor is mixed with the graphite, the mixing ratio of the amorphous carbon precursor should be appropriately selected based on the composition of the target composite particle. The amount of the amorphous carbon precursor relative to the graphite should be determined as a weight ratio ([weight of amorphous carbon] / [weight of graphite]) as the residual carbon (amorphous carbon). The weight ratio (weight of lead) × 100) is usually 0.01% or more, preferably 0.1% or more, more preferably 0.5% or more, even more preferably 1% or more, particularly preferably 2% or more, and most preferably 3% or more. On the other hand, it is preferably 30% or less, more preferably 20% or less, even more preferably 15% or less, and particularly preferably 10% or less. When this weight ratio is in the above range, the capacity is high and Li ions are easily inserted and extracted, which is preferable in terms of excellent low-temperature input / output characteristics, rapid charge / discharge characteristics, and cycle characteristics.
[0061] <Other processing> In order to produce the negative electrode material according to one embodiment of the present invention, the composite particles obtained by the above-mentioned production method may be subjected to a separate pulverization process.
[0062] Examples of coarse crushers used in the crushing process include jaw crushers, impact crushers, cone crushers, etc., examples of intermediate crushers include roll crushers, hammer mills, etc., and examples of fine crushers include ball mills, vibration mills, pin mills, stirring mills, jet mills, etc. Among these, ball mills, vibration mills, etc. are preferred from the viewpoint of short crushing time and processing speed.
[0063] The grinding speed is appropriately set depending on the type and size of the device, but for example, in the case of a ball mill, it is usually 50 rpm or more, preferably 100 rpm or more, more preferably 150 rpm or more, and even more preferably 200 rpm or more. Also, it is usually 2500 rpm or less, preferably 2300 rpm or less, and more preferably 2000 rpm or less. If the speed is too high, it tends to be difficult to control the particle size, and if the speed is too low, the processing speed tends to be slow.
[0064] The grinding time is usually 30 seconds or more, preferably 1 minute or more, more preferably 1 minute 30 seconds or more, and even more preferably 2 minutes or more. Also, it is usually 3 hours or less, preferably 2.5 hours or less, and more preferably 2 hours or less. If the grinding time is too short, it tends to be difficult to control the particle size, and if the grinding time is too long, productivity tends to decrease.
[0065] In the case of a vibration mill, the grinding speed is usually 50 rpm or more, preferably 100 rpm or more, more preferably 150 rpm or more, and even more preferably 200 rpm or more. Also, it is usually 2500 rpm or less, preferably 2300 rpm or less, and more preferably 2000 rpm or less. If the speed is too high, it tends to be difficult to control the particle size, and if the speed is too low, the processing speed tends to be slow.
[0066] The grinding time is usually 30 seconds or more, preferably 1 minute or more, more preferably 1 minute 30 seconds or more, and even more preferably 2 minutes or more. Also, it is usually 3 hours or less, preferably 2.5 hours or less, and more preferably 2 hours or less. If the grinding time is too short, it tends to be difficult to control the particle size, and if the grinding time is too long, productivity tends to decrease.
[0067] In order to produce the negative electrode material according to one embodiment of the present invention, the composite particles obtained by the above-mentioned production method may be subjected to a particle size classification treatment. The classification treatment is performed under conditions in which the mesh size is usually 53 μm or less, preferably 45 μm or less, and more preferably 38 μm or less.
[0068] There are no particular limitations on the equipment used for the classification process, but for example, in the case of dry sieving, a rotary sieve, a shaking sieve, a swirling sieve, a vibrating sieve, etc. can be used; in the case of dry airflow classification, a gravity classifier, an inertia classifier, a centrifugal classifier (classifier, cyclone, etc.), etc. can be used; and in the case of wet sieving, a mechanical wet classifier, a hydraulic classifier, a sedimentation classifier, a centrifugal wet classifier, etc. can be used.
[0069] [Negative electrode for non-aqueous secondary batteries] The negative electrode for a nonaqueous secondary battery according to one embodiment of the present invention (hereinafter, may be referred to as the "negative electrode of the present invention") comprises a current collector and an active material layer formed on the current collector, and the active material layer contains the above-mentioned negative electrode material according to one embodiment of the present invention.
[0070] To prepare a negative electrode using the above negative electrode material, the negative electrode material is mixed with a binder resin to form a slurry in an aqueous or organic medium, a thickener is added if necessary, and the slurry is applied to a current collector and dried.
[0071] The binder resin is preferably stable against non-aqueous electrolyte and insoluble in water. For example, rubber-like polymers such as styrene-butadiene rubber, isoprene rubber, and ethylene-propylene rubber; synthetic resins such as polyethylene, polypropylene, polyethylene terephthalate, polyimide, polyacrylic acid, and aromatic polyamide; thermoplastic elastomers such as styrene-butadiene-styrene block copolymers and their hydrogenated products, styrene-ethylene-butadiene, styrene copolymers, styrene-isoprene and styrene block copolymers and their hydrogenated products; soft resin-like polymers such as syndiotactic-1,2-polybutadiene, ethylene-vinyl acetate copolymers, and copolymers of ethylene and α-olefins having 3 to 12 carbon atoms; fluorinated polymers such as tetrafluoroethylene-ethylene copolymers, polyvinylidene fluoride, polypentafluoropropylene, and polyhexafluoropropylene. For example, N-methylpyrrolidone and dimethylformamide can be used as the organic medium.
[0072] The binder resin is usually used in an amount of 0.1 part by weight or more, preferably 0.2 part by weight or more, per 100 parts by weight of the negative electrode material. By using the binder resin in an amount of 0.1 part by weight or more per 100 parts by weight of the negative electrode material, the binding strength between the negative electrode materials and between the negative electrode material and the current collector becomes sufficient, and it is possible to prevent a decrease in battery capacity and a deterioration in recyclability due to the peeling of the negative electrode material from the negative electrode.
[0073] The amount of binder resin used is preferably 10 parts by weight or less, more preferably 7 parts by weight or less, per 100 parts by weight of the negative electrode material. By using 10 parts by weight or less of the binder resin per 100 parts by weight of the negative electrode material, it is possible to prevent a decrease in the capacity of the negative electrode and to prevent problems such as the impediment of the ingress and egress of alkaline ions such as lithium ions into and out of the negative electrode material.
[0074] Examples of thickeners to be added to the slurry include water-soluble celluloses such as carboxymethyl cellulose, methyl cellulose, hydroxyethyl cellulose, and hydroxypropyl cellulose, polyvinyl alcohol, and polyethylene glycol. Among these, carboxymethyl cellulose is preferred. The thickener is preferably used in an amount of usually 0.1 to 10 parts by weight, particularly 0.2 to 7 parts by weight, per 100 parts by weight of the negative electrode material.
[0075] The negative electrode current collector may be made of any material that has been known to be usable for this purpose, such as copper, copper alloy, stainless steel, nickel, titanium, carbon, etc. The current collector is usually in the form of a sheet, and it is also preferable to use a current collector having an uneven surface, a net, a punched metal, etc.
[0076] After the slurry of the negative electrode material and binder resin is applied to the current collector and dried, it is preferable to apply pressure to increase the density of the active material layer formed on the current collector, thereby increasing the battery capacity per unit volume of the negative electrode active material layer. The density of the active material layer is 1.2 g / cm 3 ~1.8g / cm 3 and preferably in the range of 1.3 g / cm 3 ~1.6g / cm 3 It is more preferable that the active material is By setting the density of the layer to the above lower limit or more, it is possible to prevent a decrease in the capacity of the battery due to an increase in the thickness of the electrode. Also, by setting the density of the active material layer to the above upper limit or less, it is possible to prevent a decrease in the rapid charge / discharge characteristics due to a decrease in the amount of electrolyte held in the voids caused by a decrease in the interparticle voids in the electrode, which reduces the mobility of alkaline ions such as lithium ions.
[0077] [Nonaqueous secondary battery] A nonaqueous secondary battery according to one embodiment of the present invention is a nonaqueous secondary battery including a positive electrode, a negative electrode, and an electrolyte, and uses the negative electrode according to one embodiment of the present invention as the negative electrode. In particular, the positive electrode and the negative electrode used in the nonaqueous secondary battery according to one embodiment of the present invention are preferably positive electrodes and negative electrodes capable of absorbing and releasing Li ions, and the nonaqueous secondary battery according to one embodiment of the present invention is preferably a lithium ion secondary battery.
[0078] The non-aqueous secondary battery according to one embodiment of the present invention can be manufactured according to a conventional method, except that the negative electrode according to one embodiment of the present invention is used. In particular, the non-aqueous secondary battery according to one embodiment of the present invention is preferably designed to have a value of [capacity of negative electrode] / [capacity of positive electrode] of 1.01 to 1.5, and more preferably 1.2 to 1.4.
[0079] [Positive electrode] As the positive electrode material serving as the positive electrode active material of the nonaqueous secondary battery according to one embodiment of the present invention, for example, lithium cobalt composite oxides having a basic composition represented by LiCoO2, lithium nickel composite oxides represented by LiNiO2, lithium transition metal composite oxides such as lithium manganese composite oxides represented by LiMnO2 and LiMn2O4, transition metal oxides such as manganese dioxide, and mixtures of these composite oxides may be used. Furthermore, TiS2, FeS2, Nb3S4, Mo3S4, CoS2, V2O5, CrO3, V3O3, FeO2, GeO2, and LiNi 0.33 Mn 0.33 Co 0.33 O2, LiFePO4, etc. can be used.
[0080] The positive electrode can be manufactured by mixing the positive electrode material with a binder resin, forming a slurry with an appropriate solvent, applying it to a current collector, and drying it. It is preferable to include a conductive material such as acetylene black or ketjen black in the slurry. If necessary, a thickener may be included. As the binder and thickener, those well known for this purpose, for example, those exemplified as those used in the manufacture of a negative electrode, can be used.
[0081] The amount of the conductive material is preferably 0.5 parts by weight to 20 parts by weight, more preferably 1 part by weight to 15 parts by weight, relative to 100 parts by weight of the positive electrode material. The amount of the thickener is preferably 0.2 parts by weight to 10 parts by weight, more preferably 0.5 parts by weight to 7 parts by weight, relative to 100 parts by weight of the positive electrode material. Furthermore, the amount of the binder resin to be added relative to 100 parts by weight of the positive electrode material is preferably 0.2 parts by weight to 10 parts by weight, more preferably 0.5 parts by weight to 7 parts by weight, when the binder resin is slurried with water, while the amount of the binder resin to be added relative to 100 parts by weight of the positive electrode material is preferably 0.5 parts by weight to 20 parts by weight, more preferably 1 to 15 parts by weight, when the binder resin is slurried with an organic solvent that dissolves the binder resin, such as N-methylpyrrolidone.
[0082] Examples of the positive electrode current collector include aluminum, titanium, zirconium, hafnium, niobium, tantalum, and alloys thereof. Among these, aluminum, titanium, tantalum, and alloys thereof are preferred, and aluminum and alloys thereof are most preferred.
[0083] [Electrolyte] The electrolyte may be prepared by dissolving various lithium salts in a conventionally known non-aqueous solvent.
[0084] As the non-aqueous solvent, for example, cyclic carbonates such as ethylene carbonate, fluoroethylene carbonate, propylene carbonate, butylene carbonate, and vinylene carbonate; chain carbonates such as dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate; cyclic esters such as γ-butyrolactone; cyclic ethers such as crown ether, 2-methyltetrahydrofuran, tetrahydrofuran, 1,2-dimethyltetrahydrofuran, and 1,3-dioxolane; chain ethers such as 1,2-dimethoxyethane, and the like may be used. Usually, two or more of these are mixed and used. Among them, it is preferable to use a cyclic carbonate and a chain carbonate, or to further mix them with other solvents.
[0085] The electrolyte may contain compounds such as vinylene carbonate, vinyl ethylene carbonate, succinic anhydride, maleic anhydride, propane sultone, diethyl sulfone, and difluorophosphates such as lithium difluorophosphate, as well as overcharge inhibitors such as diphenyl ether and cyclohexylbenzene.
[0086] Examples of electrolytes to be dissolved in the non-aqueous solvent include LiClO4, LiPF6, LiBF4, LiCF3SO3, LiN(CF3SO2)2, LiN(CF3CF2SO2)2, LiN(CF3SO2)(C4F9SO2), and LiC(CF3SO2)3. The concentration of the electrolyte in the electrolytic solution is usually 0.5 mol / L to 2 mol / L, and preferably 0.6 mol / L to 1.5 mol / L.
[0087] [Separator] In the nonaqueous secondary battery according to one embodiment of the present invention, a separator is preferably used between the positive electrode and the negative electrode, and as such a separator, a porous sheet or nonwoven fabric made of polyolefin such as polyethylene or polypropylene is preferably used. EXAMPLES
[0088] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples as long as it does not deviate from the gist of the invention. Note that the values of various manufacturing conditions and evaluation results in the following examples are meant as preferred upper or lower limit values in the embodiments of the present invention, and the preferred range may be a range defined by a combination of the above-mentioned upper or lower limit values and the values of the following examples or values between the examples.
[0089] <Preparation of negative electrode sheet> The negative electrode material prepared under the conditions described below was used as the negative electrode active material, and the active material layer density was 1.5±0.03 g / cm 3Specifically, 50.00±0.02g of negative electrode material, 50.00±0.02g of 1% by weight sodium carboxymethylcellulose solution (0.500g in solid content), and 1.00±0.05g of styrene-butadiene rubber aqueous dispersion with a weight-average molecular weight of 270,000 (0.5g in solid content) were mixed in a Keyence hybrid mixer for 5 minutes and degassed for 30 seconds to obtain a slurry.
[0090] This slurry was applied to a 10 μm thick copper foil current collector so that the negative electrode material was 10.00 ± 0.2 mg / cm 2 The mixture was applied to a width of 10 cm using a die coater so that it would adhere to the substrate. After drying, the mixture was cut to a width of 5 cm and roll pressed using a roller with a diameter of 20 cm to obtain an active material layer density of 1.5±0.03 g / cm. 3 The electrode sheet was obtained by adjusting the thickness so as to be equal to or larger than the thickness.
[0091] <Preparation of positive electrode sheet> The positive electrode was fabricated as follows. First, 85% by weight of lithium nickel-manganese-cobalt oxide (LiNiMnCoO2) as a positive electrode active material, 10% by weight of acetylene black as a conductive material, and 5% by weight of polyvinylidene fluoride (PVdF) as a binder were mixed in N-methylpyrrolidone solvent to obtain a slurry. This slurry was then applied to a current collector having a thickness of 100 μm. The positive electrode material is 22.5±0.2mg / cm on 15μm aluminum foil. 2 The mixture was applied using a blade coater so that the mixture would adhere well, and then dried at 130° C. The mixture was then roll pressed to obtain a positive electrode density of 2.60±0.05 g / cm. 3 The electrode sheet was obtained by adjusting the thickness so as to be equal to or larger than the thickness.
[0092] <Method of manufacturing non-aqueous secondary batteries (laminated type batteries)> The negative electrode material prepared by the above method has a density of 10.0±0.3mg / cm 2 The density of the attached active material layer is 1.5±0.03g / cm 3The negative electrode sheet, positive electrode sheet, and polyethylene separator were laminated in the order of negative electrode, separator, positive electrode. The battery element thus obtained was wrapped in a cylindrical aluminum laminate film, and an electrolyte solution in which LiPF6 was dissolved in a mixed solvent of ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) (volume ratio = 3:3:4) to a concentration of 1 mol / L was injected, followed by vacuum sealing to produce sheet-shaped non-aqueous secondary batteries. Furthermore, in order to increase the adhesion between the electrodes, the sheet-shaped battery was sandwiched between glass plates and pressure was applied.
[0093] <How to make a non-aqueous secondary battery (coin battery)> The negative electrode material prepared by the above method has a density of 10.0±0.3mg / cm 2 The density of the attached active material layer is 1.5±0.03g / cm 3 The electrode sheet was punched into a disk with a diameter of 12.5 mm to serve as the negative electrode, and lithium metal foil was punched into a disk with a diameter of 14 mm to serve as the counter electrode. Between the two electrodes, a separator (made of porous polyethylene film) was placed, which was impregnated with an electrolyte solution in which LiPF6 was dissolved at 1 mol / L in a mixed solvent of ethylene carbonate and ethyl methyl carbonate (volume ratio = 3:7), and a 2016 coin-type battery was fabricated.
[0094] <Discharge capacity (mAh / g)> Using the non-aqueous secondary battery (2016 coin type battery) prepared by the above method, the capacity during battery charge and discharge was measured by the following measurement method.
[0095] The battery was charged to 5 mV against the lithium counter electrode at a current density of 0.05 C, and further charged at a constant voltage of 5 mV until the current density reached 0.005 C. After doping lithium into the negative electrode, the battery was discharged to 1.5 V against the lithium counter electrode at a current density of 0.1 C. The discharge capacity per weight of the negative electrode active material at this time was taken as the discharge capacity (mAh / g) of this material.
[0096] <Cycle swelling> For non-aqueous secondary batteries that had not undergone charge-discharge cycles, three cycles were performed at 25°C with a voltage range of 4.1V to 3.0V and a current value of 0.2C (the current value at which the rated capacity based on the discharge capacity at one-hour rate is discharged in one hour is 1C, the same applies below), and two cycles were performed with a voltage range of 4.2V to 3.0V and a current value of 0.2C (constant voltage charging at 4.2V for an additional 2.5 hours during charging). At this point, the glass plate for fixing the battery was removed, and the thickness was measured at nine points for each battery using a contact thickness meter manufactured by Mitutoyo Corporation, and the average was taken as the "thickness before cycling." After that, the battery was sandwiched between glass plates again, and a cycle test was performed by charging and discharging the battery 25 times in a thermostatic chamber at 45°C under the conditions of 0.8C-CCCV charging, 0.8CCC discharging, and 1.5V cut. After that, the battery in a SOC 0% state was measured at the same nine locations as before the cycling, and the average was calculated as the "thickness after cycling", and the cycle swelling = {(thickness after cycling) / (thickness before cycling)-1} x 100 (%).
[0097] <Quick charging characteristics> For coin type batteries that had not undergone charge / discharge cycles, we performed initial charge / discharge at 25°C for three cycles at a voltage range of 4.1V to 3.0V and a current value of 0.2C (the current value at which the rated capacity based on the discharge capacity at one-hour rate is discharged in one hour is 1C, and so on below), and two cycles at a voltage range of 4.2V to 3.0V and a current value of 0.2C (when charging, constant voltage charging was performed at 4.2V for an additional 2.5 hours). After that, we performed CC charging from a state of 0% SOC to 100% SOC at a current value of 3C. The dV / dQ value was calculated from the derivative of the obtained voltage (V) - capacity (Q) curve, and the capacity value when the dV / dQ value changes from the negative region to the positive region, dV / dQ = 0, was determined, and the fast charging characteristic was calculated as {capacity value (mAh) when dV / dQ = 0} / {capacity value (mAh) at SOC 100%} x 100 (%).
[0098] Example 1 Scaly natural graphite with an average particle size (d50) of 100 μm was pulverized to obtain scaly natural graphite with a d50 of 11.1 μm. 100 parts by weight of the obtained scaly natural graphite was mixed with 12 parts by weight of liquid oil as a granulating agent, and then spheroidized treatment was performed. The granulating agent was removed by heat treatment to obtain spherical natural graphite. The obtained spherical graphite was filled and sealed in a rubber container and subjected to isostatic pressure treatment at 200 MPa to control the amount of mercury discharged / the amount of mercury injected (B / A). The obtained molded product was crushed and classified. Various physical properties of the obtained spherical graphite powder (negative electrode material raw material) are shown in Table 1. The amount of mercury discharged / the amount of mercury injected (B / A) × 100 (%) in the above-mentioned mercury porosimetry was 61.5%. The spheroidized graphite powder was mixed with pitch adjusted to 0.02% ash by weight, 20 ppm metal impurities by weight, and 1% Qi by weight as an amorphous carbon precursor, and the pressure in the furnace was reduced to 10 torr or less, and the pressure was returned to atmospheric pressure with nitrogen. Nitrogen was then circulated to make the oxygen concentration in the furnace <100 ppm, and heat treatment was performed at 1300°C in an inert gas. The obtained fired product was crushed and classified to obtain a composite carbon material containing amorphous carbonaceous material on the surface of the graphite particles. From the firing yield, it was confirmed that the weight ratio of the spheroidized graphite particles to amorphous carbon (spheroidized graphite particles: amorphous carbon) in the obtained composite carbon material was 1:0.08. Various physical properties of the negative electrode material obtained in this manner are shown in Table 1. In addition, the discharge capacity, cycle swelling, and rapid charging characteristics described above were measured using the obtained negative electrode material. The results are shown in Table 1. Note that A and B in Table 1 indicate values rounded off to the fourth decimal place.
[0099] Example 2 Scaly natural graphite with an average particle size (d50) of 100 μm was pulverized to obtain scaly natural graphite with a d50 of 8.5 μm. The obtained scaly natural graphite was mixed with 12 parts by weight of liquid oil as a granulating agent, and then subjected to a spheroidizing treatment. The granulating agent was removed by heat treatment to obtain spheroidized natural graphite. The obtained spheroidized graphite was filled and sealed in a rubber container and subjected to an isostatic pressurization treatment at 200 MPa to control the amount of mercury discharged / the amount of mercury forced in (B / A). The obtained molded product was crushed and classified. Various physical properties of the obtained spheroidized graphite powder (negative electrode raw material) are shown in Table 1. The amount of mercury discharged / the amount of mercury forced in (B / A) × 100 (%) in the mercury porosimetry was 69.9%. The spheroidized graphite powder was mixed with pitch adjusted to 0.02% by weight ash, 20 ppm by weight metal impurities, and 1% by weight Qi as an amorphous carbon precursor, and the pressure in the furnace was reduced to 10 torr or less, and then the pressure was returned to atmospheric pressure with nitrogen. Nitrogen was then circulated to make the oxygen concentration in the furnace <100 ppm, and heat treatment was performed at 1300°C in an inert gas. The obtained fired product was crushed and classified to obtain a composite carbon material containing amorphous carbonaceous material on the surface of the graphite particles. From the firing yield, it was confirmed that the weight ratio of the spheroidized graphite particles to amorphous carbon (spheroidized graphite particles: amorphous carbon) in the obtained composite carbon material was 1:0.06. Various physical properties of the negative electrode material obtained in this manner are shown in Table 1. In addition, the discharge capacity, cycle swelling, and rapid charging characteristics described above were measured using the obtained negative electrode material. The results are shown in Table 1.
[0100] Comparative Example 1 Spherical natural graphite (average particle size (d50) 16.2 μm, BET specific surface area (SA) 6.9 m) was produced by spheroidizing flake natural graphite with an average particle size (d50) of 100 μm. 2 / g, tap density 1.00g / cm 3 The mercury discharge amount / mercury intrusion amount (B / A) × 100 (%) of the obtained spherical graphite powder (negative electrode raw material) in the mercury porosimetry was 27.5%. This spherical graphite powder and an amorphous carbon precursor with an ash content of <0.01% and a metal impurity content of 6. After mixing the tar adjusted to 0 ppm and Qi<0.1%, the pressure inside the furnace was reduced to 10 torr or less, and then the pressure was returned to atmospheric pressure with nitrogen. Nitrogen was then circulated to adjust the oxygen concentration inside the furnace to <100 ppm, and heat treatment was performed at 1300°C. The obtained fired material was crushed and classified to obtain a composite carbon material containing amorphous carbonaceous matter on the surface of graphite particles. From the firing yield, it was confirmed that the weight ratio of the spherical graphite particles to the amorphous carbon (spheroidal graphite particles: amorphous carbon) in the obtained anode material (composite carbon material) was 1:0.03. The above-mentioned discharge capacity, cycle swelling, and rapid charging characteristics were measured using the anode material obtained in this way. The results are shown in Table 1.
[0101] Comparative Example 2 Spherical natural graphite (average particle size (d50) 10.9 μm, BET specific surface area (SA) 8.1 m) was obtained by spheroidizing flake natural graphite with an average particle size (d50) of 100 μm. 2 / g, tap density 0.90g / cm 3 ) was obtained. The mercury outflow amount / mercury intrusion amount (B / A) × 100 (%) of the obtained spherical graphite powder in the mercury porosimetry was 28.3%. After mixing this spherical graphite powder with tar adjusted to ash content <0.01%, metal impurity content 60 ppm, and Qi <0.1% as an amorphous carbon precursor, the pressure in the furnace was reduced to 10 torr or less, and the pressure was returned to atmospheric pressure with nitrogen, and nitrogen was further circulated to set the oxygen concentration in the furnace to <100 ppm, and a heat treatment was performed at 1300 °C. The obtained fired product was crushed and classified to obtain a negative electrode material, which is a composite carbon material containing amorphous carbonaceous material on the surface of graphite particles. From the firing yield, it was confirmed that the weight ratio of the spherical graphite particles to amorphous carbon (spherical graphite particles: amorphous carbon) in the obtained negative electrode material (composite carbon material) was 1:0.04. The negative electrode material thus obtained was used to measure the discharge capacity, cycle swelling, and rapid charging characteristics described above. The results are shown in Table 1.
[0102] Comparative Example 3 Spherical natural graphite (average particle size (d50) 7.2 μm, BET specific surface area (SA) 11.1 m) was obtained by spheroidizing flake natural graphite with an average particle size (d50) of 100 μm.2 / g, tap density 0.81g / cm 3 ) was obtained. The mercury outflow amount / mercury intrusion amount (B / A) × 100 (%) of the obtained spherical graphite powder in the mercury porosimetry was 41.2%. After mixing this spherical graphite powder with tar adjusted to ash content <0.01%, metal impurity content 60 ppm, and Qi <0.1% as an amorphous carbon precursor, the pressure in the furnace was reduced to 10 torr or less, and the pressure was returned to atmospheric pressure with nitrogen, and nitrogen was further circulated to set the oxygen concentration in the furnace to <100 ppm, and a heat treatment was performed at 1300 °C. The obtained fired product was crushed and classified to obtain a negative electrode material, which is a composite carbon material containing amorphous carbonaceous material on the surface of graphite particles. From the firing yield, it was confirmed that the weight ratio of the spherical graphite particles to amorphous carbon (spherical graphite particles: amorphous carbon) in the obtained negative electrode material (composite carbon material) was 1:0.03. The negative electrode material thus obtained was used to measure the discharge capacity, cycle swelling, and rapid charging characteristics described above. The results are shown in Table 1.
[0103] Comparative Example 4 The discharge capacity, cycle swelling, and rapid charging characteristics described above were measured using artificial graphite containing amorphous carbon on the surface. The results are shown in Table 1.
[0104] [Table 1]
[0105] The relationship between the amount of mercury discharged / the amount of mercury injected (B / A) and the cycle swelling in Examples 1 to 2 and Comparative Examples 1 to 3 is shown in FIG. 1. This makes it possible to obtain a lithium ion secondary battery with high discharge capacity, suppressed cycle swelling, and excellent rapid charging characteristics. [Industrial Applicability]
[0106] The negative electrode material for non-aqueous secondary batteries and the negative electrode material for non-aqueous secondary batteries of the present invention, as well as the negative electrodes for non-aqueous secondary batteries and non-aqueous secondary batteries containing the same, have high capacity, small cycle swelling, and excellent rapid charge / discharge characteristics, and can therefore be suitably used for in-vehicle applications; power tool applications; and portable device applications such as mobile phones and personal computers.
Claims
1. A negative electrode material for a non-aqueous secondary battery, comprising a raw material for a negative electrode material for a non-aqueous secondary battery, the raw material containing graphite, and the ratio of the following formula (1) being 50% or more, where A is the amount of mercury injected and B is the amount of mercury released, obtained by mercury injection porosimetry: Raman R calculated from the following formula α 1 The negative electrode material for a non-aqueous secondary battery has a value of 0.15 or more and 1.00 or less. Formula (1) B / A×100(%) Formula α: [Raman R 1 value] = [1360 cm in Raman spectroscopy -1 Nearby peaks P B Intensity I B ] / [1580cm -1 Nearby peaks P A Intensity I A ]
2. 2. The negative electrode material for a nonaqueous secondary battery according to claim 1, wherein the amount of mercury intrusion A is 0.001 mL / g or more and 0.5 mL / g or less.
3. 3. The negative electrode material for a non-aqueous secondary battery according to claim 1, wherein the amount of mercury discharged B is 0.0005 mL / g or more and 0.5 mL / g or less.
4. The tap density of the raw material for the negative electrode material for non-aqueous secondary batteries is 0.7 g / cm 3 Above, 1.4g / cm 3 The negative electrode material for a non-aqueous secondary battery according to any one of claims 1 to 3, wherein:
5. The nonaqueous secondary battery negative electrode material according to any one of claims 1 to 4, wherein the interplanar spacing (d002) obtained by X-ray diffraction is 0.34 nm or less, and the crystallite size (Lc) in the c-axis direction is 90 nm or more.
6. A non-aqueous secondary battery using the negative electrode material according to any one of claims 1 to 5.
Citation Information
Patent Citations
Natural graphite-based modified composite material and preparation method thereof, and lithium ion battery comprising modified composite material
CN108063229A
Graphite material for lithium ion secondary battery, and method for manufacturing the same
JP2011060465A
Carbon particle for lithium ion secondary battery negative electrode, negative electrode for lithium ion secondary battery, and lithium ion secondary battery
JP2014135287A
Carbon material and nonaqueous secondary battery
JP2016178074A
Carbon material and nonaqueous secondary battery
JP2016186913A